Chemical constituents with antimicrobial and antioxidant activity from the aerial parts of Callistemon lanceolatus (Sm.) Sweet. Issue 22 (16th November 2020) - Nazreen, Syed; Mahboob Alam, Mohammad; Hamid, Hinna; Ali, Mohammad; Sarwar Alam, Mohammad
Abstract: Callistemon lanceolatus (Sm.) Sweet grows all over the world and used to treat cough and bronchitis. The air-dried powder of the aerial parts was exhaustively extracted with methanol and the concentrated extract was adsorbed on silica gel for preparation of slurry. It was dried and subjected to silica gel column packed in petroleum ether. The column was eluted with organic solvents in order of increasing polarity to isolate 1-triacosanol (1 ), n -eicosanyl palmitate (2 ), n -heptadecanyl arachidate (3 ), n -tricosanyl palmitate, (4 ), 4-hydroxyphenethyl carbocerate (5 ), 4-hydroxyphenethyl gheddate (6 ), urs-12-en-3 α -acetoxy-18 β -H-28-oic acid (7 ) and stigmast-5-en-3 β -ol-3 β -D-glucuronopyranoside (8 ). Among them, compound 5 and 6 were new fatty acid ester isolated from this plant. Compound 7 showed MIC 32 µg/mL against E. coli which was comparable to amoxicillin having same MIC 32 µg/mL. Compound 5 and 6 showed significant antioxidant activity by inhibiting DPPH due to the presence of phenolic groups. Graphical Abstract: